Imitated alveolar bone-periodontal membrane biphasic stent as well as preparation method and application thereof

Through the imitation alveolar bone-perioperipart biphasic scaffold, a nanoclay assembly of dopamine-modified gelatin and lyophilized platelet-rich fibrin exudate was formed to form a composite scaffold, which solved the bone tissue reconstruction and growth factor in periodontal tissue regeneration. The problem of release achieves synchronous repair and efficient regeneration of periodontal tissue.

CN119113213APending Publication Date: 2024-12-13FOURTH MILITARY MEDICAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411285292.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing periodontal regeneration technology cannot effectively reconstruct and regenerate periodontal soft and hard tissue, especially bone tissue, and the existing stent materials cannot preserve and release growth factors for a long time, limiting their application in periodontal tissue engineering.

Method used

Using imitation alveolar bone-periosteal membrane biphasic scaffolds, including an ordered fiber network fiber phase module constructed with dopamine-modified gelatin and a nanoclay gelatin 3D printed bone phase module doped with lyophilized platelet-rich fibrin exudate, through UV cross-linking forms a composite scaffold that matches the biomechanical characteristics of periodontal tissue.

Benefits of technology

The synchronous repair of periodontal hard and soft tissues is achieved, the regeneration efficiency and mechanical strength of the scaffold is improved, stem cells can be recruited and bone differentiation can be promoted, complex anatomical structures of natural tissues can be simulated, and the shortcomings of the existing technology are made up for.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119113213A_ABST
    Figure CN119113213A_ABST
Patent Text Reader

Abstract

The invention relates to an alveolar bone-periodontal membrane imitating dual-phase scaffold and a preparation method and application thereof, and relates to the technical field of tissue engineering scaffold materials, the alveolar bone-periodontal membrane imitating dual-phase scaffold comprises a fiber phase module and a bone phase module constructed on the fiber phase module; the fiber phase module is an ordered arrangement fiber network scaffold constructed by dopamine modified gelatin; the bone phase module is a gelatin 3D printing bracket doped with freeze-dried platelet-rich fibrin percolate and nano clay. The artificial alveolar bone-periodontal membrane biphase stent provided by the invention comprises a bone phase module of a PRFe-loaded 3D printing stent and a fiber phase module of oriented electrostatic spinning, and each module is highly matched with biomechanical characteristics of periodontal soft and hard tissues, so that synchronous repair of the periodontal soft and hard tissues can be realized; the technical problems that a gap exists between tissue engineering scaffold interface bionics and natural tissues and the endogenous regeneration efficiency is poor are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tissue engineering scaffold materials, and in particular to an alveolar bone-periodontal ligament imitation dual-phase scaffold and a preparation method and application thereof. Background Art

[0002] Periodontitis is a chronic inflammation of the soft and hard supporting tissues around the teeth, namely the alveolar bone, periodontal ligament and cementum, and is the main cause of tooth loss in adults. The incidence of late-stage periodontitis is extremely high, but there is currently a lack of effective treatments. Traditional periodontal treatment methods mechanically remove pathogenic factors such as plaque and tartar from local periodontal tissues to control the development of inflammation, but they cannot reconstruct and regenerate the lost periodontal soft and hard tissues, especially bone tissue. The periodontal regeneration strategies currently used in clinical practice, such as guided bone regeneration, have shortcomings such as narrow indications, poor predictability, and rapid release of bioactive substances, resulting in uncertain clinical manifestations and cannot meet current clinical needs. The introduction of tissue engineering technology into the field of periodontal regeneration has increasingly become a research focus and direction in recent years, bringing new hope for preserving teeth with late-stage periodontitis.

[0003] Natural periodontal tissue is a periodontal complex composed of alveolar bone, cementum and periodontal ligament. It has a highly complex multi-level structure and is the key to the current difficulty in periodontal tissue regeneration. Corresponding to the complex anatomical structure, each tissue has distinct biomechanical characteristics, which is reflected in the huge biomechanical differences between soft and hard tissues. More importantly, periodontal tissue remodeling involves a series of complex growth factor regulation. Therefore, the ideal periodontal tissue regeneration scaffold will use the biomechanical characteristics of natural tissue as a template to construct a multiphase bionic scaffold, and at the same time have multiple biological induction activities.

[0004] Platelet-rich fibrin (PRF) is a product of autologous whole blood centrifugation and is considered to be an autologous graft. It is rich in a variety of cytokines, including platelet-derived growth factor-AB (PDGF-AB), transforming growth factor-β1 (TGF-β1) and human bone morphogenetic protein-2 (BMP 2), which have the effect of promoting bone remodeling and soft tissue healing. PRF is simple to prepare and does not require the addition of any artificial agents, avoiding the risk of cross-infection. At present, PRF is widely used in the repair of soft tissue defects and bone tissue defects in the field of periodontal tissue regeneration. However, PRF needs to be used immediately after production, cannot be stored for a long time, the release time of growth factors is shorter than the bone tissue healing process, and the mechanical strength is poor, which limits its single application in bone tissue engineering. Therefore, extracting growth factors from PRF and then prolonging the release of growth factors and improving mechanical strength has become a research hotspot. Since PRF exudate (PRFe) is the main source of growth factors, the stability of bioactive factors in PRFe can be improved by freeze-drying and long-term storage. Compared with freshly prepared PRF, freeze-dried PRFe has significant advantages in tissue engineering, including adjustable factor concentration and compounding of multiple biomaterials.

[0005] Currently, there are no reports in the prior art on loading PRFe onto a biphasic bionic scaffold that matches the biomechanical properties of alveolar bone-periodontal ligament. Summary of the invention

[0006] In order to solve the above problems, the present invention provides an alveolar bone-periodontal ligament imitation biphasic scaffold and a preparation method and application thereof.

[0007] In a first aspect, the present invention provides an alveolar bone-periodontal ligament-mimicking biphasic scaffold, the alveolar bone-periodontal ligament-mimicking biphasic scaffold comprising a fiber phase module and a bone phase module constructed on the fiber phase module;

[0008] The fiber phase module is an orderly arranged fiber network scaffold constructed by dopamine-modified gelatin;

[0009] The bone phase module is a gelatin 3D printed scaffold doped with freeze-dried platelet-rich fibrin exudate and nanoclay.

[0010] Furthermore, the thickness of the fiber phase module is 0.1-0.3 mm, and the thickness of the bone phase module is 4-6 mm.

[0011] Furthermore, the fiber phase module and the bone phase module are compositely connected by ultraviolet cross-linking.

[0012] In a second aspect, the present invention provides a method for preparing the alveolar bone-periodontal ligament-mimicking biphasic scaffold according to any one of the first aspects, the preparation method comprising the following steps:

[0013] Adding freeze-dried platelet-rich fibrin exudate, nanoclay and gelatin into a first solvent for a first mixing reaction to obtain a 3D printing ink;

[0014] adding dopamine, EDC, NHS and gelatin into a second solvent for a second mixing reaction, and then adding an acetic acid solution for stirring to obtain a dopamine-modified gelatin electrospinning solution;

[0015] The dopamine-modified gelatin electrospinning solution is prepared by an electrospinning method to obtain an ordered fiber network membrane;

[0016] After drying the ordered fiber network membrane, immersing it in a photoinitiator solution, and then performing a first ultraviolet crosslinking to obtain a fiber phase module;

[0017] The 3D printing ink is printed on the fiber phase module through a 3D printing device to construct a bone phase module, and then a second ultraviolet cross-linking is performed to obtain the alveolar bone-periodontal membrane simulated biphasic scaffold.

[0018] Furthermore, the 3D printing ink includes the following components in percentage by mass:

[0019] 0.1%-1.5% of freeze-dried platelet-rich fibrin exudate, 0.5%-3% of nanoclay, 12-22% of gelatin; the remainder is the first solvent;

[0020] Wherein, the nanoclay includes Laponite-XLG (abbreviated as Laponite), the gelatin includes methacrylamide gelatin, and the first solvent includes at least one of PBS culture medium, MEM culture medium, PBS solution and MEM solution.

[0021] Further, the dopamine-modified gelatin electrospinning solution includes the following components in percentage by mass:

[0022] Dopamine (1%-3%), EDC / NHS (0.5%; wherein the molar ratio of EDC to NHS is (5-3):1), gelatin 15-25%; the volume concentration of the acetic acid solution is 27-33vt%; the volume concentration of the acetic acid solution is 27-33vt%; the second solvent comprises at least one of hexafluoroisopropanol and formic acid; the dopamine comprises dopamine hydrochloride.

[0023] Furthermore, the working condition parameters of the electrospinning method include: collecting the oriented electrospinning by using an oriented receiver roller, the electrospinning process parameters are set to a voltage of 18-25 kV, a distance of 10 to 20 cm between the spinning needle and the receiver, a syringe needle of 18-22 G, an injection speed of 0.3-1.2 ml / h, and an oriented receiver roller speed of 2800-3200 rpm.

[0024] Furthermore, the working condition parameters of the 3D printing device include: the diameter of the extruded wire is 0.1-0.4 mm, and the 3D printer parameters are set to: the bracket size is 10×10×5 mm 3 , push-out air pressure 20 bar, needle temperature 25°C, receiving platform temperature 5°C, needle speed 4 mm / s, layer spacing 0.26 mm, and printing filament spacing 1 mm.

[0025] Furthermore, the photoinitiator solution is an ethanol solution containing photoinitiator 2959, and the mass concentration of the photoinitiator 2959 is 1-3%; the working condition parameters of the first UV cross-linking include: the UV cross-linking time is 50 to 70 minutes; the working condition parameters of the second UV cross-linking include: the UV cross-linking time is 20 to 40 seconds.

[0026] In a third aspect, the present invention provides a use of the alveolar bone-periodontal ligament-mimicking biphasic scaffold described in any one of the first aspect and the second aspect in the preparation of products for treating and repairing soft and hard tissue defects.

[0027] The above technical solution provided by the embodiment of the present invention has at least the following advantages compared with the prior art:

[0028] The embodiment of the present invention provides an alveolar bone-periodontal ligament-mimicking dual-phase scaffold and its preparation method and application. The alveolar bone-periodontal ligament-mimicking dual-phase scaffold provided by the present invention includes a bone phase module of a 3D printed scaffold loaded with PRFe and a fiber phase module of oriented electrospinning. Each module highly matches the biomechanical characteristics of periodontal soft and hard tissues, and can achieve synchronous repair of periodontal hard and soft tissues, effectively solving the gap between the interface bionics of tissue engineering scaffolds and natural tissues and the technical problem of poor endogenous regeneration efficiency, making up for the deficiencies of the prior art. Specifically:

[0029] 1. In the present invention, the biphasic scaffold is composed of a bone phase module of a 3D printed scaffold loaded with PRFe and a fiber phase module of oriented electrospinning. Each module highly matches the biomechanical characteristics of periodontal hard and soft tissues, and can achieve synchronous repair of periodontal hard and soft tissues. Compared with a single-phase scaffold, i.e., a single electrospun fiber membrane or a 3D printed scaffold material, the biphasic scaffold has a better application prospect.

[0030] 2. The interface of the biphasic scaffold in the present invention is composed of interwoven nanofibers that cross and penetrate the bone phase modules. The biphasic interfaces are mutually fused and penetrated without obvious boundaries, highly simulating the interface of natural soft and hard tissues. Compared with gradient gel or hierarchical fiber composite scaffolds, the biphasic scaffold is highly bionic to the natural complex anatomical structure and is expected to achieve interface remodeling.

[0031] 3. The bone phase module of the biphasic scaffold in the present invention is a 3D printed material loaded with PRFe, which can meet the customized needs according to the shape of the defect site, and has the function of recruiting stem cells and promoting bone differentiation; the fiber phase module in the biphasic scaffold has a highly oriented fiber structure, which can effectively guide cell arrangement and promote the differentiation of periodontal ligament stem cells into periodontal ligament, thereby realizing the integrated repair of periodontal soft and hard tissues.

[0032] 4. The biphasic scaffold of the present invention highly matches the biomechanical characteristics of periodontal soft and hard tissues, wherein the bone phase scaffold loaded with PRFe can release a variety of bioactive substances, and the physically doped nanoclay further enhances the hardness of the bone phase module to match the hardness of the alveolar bone; the fiber phase module is composed of GelMA modified by dopamine, and the chemical grafting of dopamine enhances the cross-linking density of GelMA to improve its viscoelasticity to match the viscoelasticity of the periodontal membrane, thereby obtaining a biomechanical gradient change similar to that of natural tissue

[0033] In summary, the present invention provides an alveolar bone-periodontal ligament-imitative biphasic scaffold based on 3D printing and electrostatic spinning technology, and its preparation method and application. The bone phase module is constructed by 3D printing to recruit stem cells and differentiate into osteoblasts; the fiber phase module composed of an oriented fiber network is obtained by electrostatic spinning technology to guide the directional arrangement of stem cells and differentiate into ligaments; and the cross-linking is induced by ultraviolet light to finally form an alveolar bone-periodontal ligament-imitative biphasic scaffold. The bone phase module has the ability to recruit stem cells and promote osteoblast differentiation; the fiber phase module can directional guide cell arrangement and promote the differentiation of stem cells into periodontal ligaments, thereby effectively promoting the regeneration of the periodontal tissue complex. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0036] The schematic diagram of the alveolar bone-periodontal ligament-mimicking dual-phase scaffold structure shows that the dual-phase scaffold is composed of a bone phase module of a 3D printed scaffold and a fiber phase module of oriented electrospinning. The enlarged image on the right shows the microscopic morphology of the alveolar bone-periodontal ligament-mimicking dual-phase scaffold, in which the red box shows the microscopic porous morphology of the bone phase module of the 3D printed scaffold; the green box shows the highly ordered fiber network morphology of the fiber phase module of oriented electrospinning; the yellow box shows the bionic structural morphology of the fibers crossing through the bone phase module at the characteristic dual-phase interface junction.

[0037] Figure 1 A schematic flow chart of a method for preparing an alveolar bone-periodontal ligament-mimicking dual-phase scaffold provided in an embodiment of the present invention.

[0038] Figure 2 A schematic diagram and representation of 3D printing preparation of a bone phase module of freeze-dried platelet-rich fibrin exudate (PRFe) incorporated into a dual-phase scaffold of alveolar bone-periodontal ligament imitation based on 3D printing and electrospinning technology provided in an embodiment of the present invention; Figure 2 Middle: A is a schematic diagram of 3D printed GelMA / Laponite scaffolds containing 0.5%, 1% and 2% nanoclay. The hardness mechanical properties of the GelMA scaffolds were enhanced by physical doping with nanoclay. The GelMA scaffolds without nanoclay were used as controls; B are representative images of optical and scanning electron microscopy (SEM), showing the overall morphology and surface microstructure of GelMA, GL-0.5, GL-1 and GL-2; Top row: Overall view of the 3D printed scaffolds observed by optical microscopy (10×, stereo microscope; scale bar: 5 mm); Middle row: Surface microstructure of the 3D printed scaffolds (middle: 50×, SEM; scale bar: 500 μm; bottom row: 500×, SEM; scale bar: 500 μm). EM, scale bar: 50 μm); C is elemental analysis (EDS), showing that silicon (Si) and magnesium (Mg) elements in the 3D printed GL-2 scaffold (500×, SEM; scale bar: 50 μm) are uniformly distributed on the scaffold surface; D is the swelling rate of GelMA, GL-0.5, GL-1 and GL-2 (n=3) and E is the degradation curve; F is the compressive stress-strain curve of GelMA, GL-0.5, GL-1 and GL-2 and G is the initial compression modulus calculated according to the compression curve (n=3); the results are expressed as mean ± SD, and the data shown in D and G were analyzed by one-way ANOVA, *p<0.05, **p<0.01 and ***p<0.001 indicate statistical differences among the groups.

[0039] Figure 3 Schematic diagram and characterization of the preparation of the bioactivated GelMA / Laponite scaffold in the embodiment of the present invention, the incorporation of freeze-dried platelet-rich fibrin exudate (PRFe) enhances the cell recruitment and osteogenic activity of the 3D printed osteophase module containing 2% Laponite (GL-2); Figure 3Middle: A is a schematic diagram of the preparation of PRFe; B is a representative image of the method steps involved in the preparation of PRFe; (i) whole blood collection, (ii) platelet-rich fibrin (PRF) between the platelet-poor plasma layer and the red blood cell debris layer after centrifugation, (iii) the gross view of the PRF clot, (iv) the gross view of the PRF clot after compression, (v) PRF exudate (PRFe) collected in an EP tube, (vi) the gross view of freeze-dried PRFe; C is TGF-β1 and BMP in GL-2+PRFe -2 cumulative release curve (n = 3) (ELISA method); D is a representative image of the scratch healing assay showing the PDLSCs migrating in the conditioned medium of GL-2 and GL-2 + PRFe (40×, inverted microscope; scale bar: 500 μm); E is a representative image of crystal violet staining showing the PDLSCs migrating under the condition of co-culture with GL-2 and GL-2 + PRFe (100×, inverted microscope; scale bar: 200 μm); F is a quantitative analysis showing the PDLSCs migrating under the condition of co-culture with GL-2 and GL-2 + PRFe at 12 hours and 2 The percentage of wound closure area after 4 hours of incubation (n=3); G is the quantitative analysis of PDLSC migration to the other side of the membrane after 48 hours of co-culture (n=3); H is the representative images of ALP staining of PDLSCs cultured on GL-2 and GL-2+PRFe after 7 days of osteogenic induction (upper row of figures: 40×, inverted microscope; scale bar: 500μm; lower row of figures: 100×, inverted microscope; scale bar: 200μm); I is the representative images of ALP staining of PDLSCs cultured on GL-2 and GL-2+PRFe after 21 days of osteogenic induction. Representative images of ARS staining in PDLSCs cultured on 2+PRFe (upper row of figures: 40×, inverted microscope; scale bar: 500 μm; lower row of figures: 100×, inverted microscope; scale bar: 200 μm); the results are expressed as mean ± SD, data shown in F were analyzed by two-way ANOVA; data shown in G were analyzed by one-way ANOVA, *p<0.05, **p<0.01 and ***p<0.001 indicate statistical differences among the groups.

[0040] Figure 4 The infrared spectrum and characterization of the dopamine-modified GelMA (GelMA-DA) fiber network prepared by electrospinning technology of the fiber phase module in the alveolar bone-periodontal ligament dual-phase scaffold based on 3D printing and electrospinning technology provided in the embodiment of the present invention; GelMA modified with 1% DA (GD-1) and 2% DA (GD-2) were studied, and the electrospun GelMA fiber network without DA modification was used as a control; Figure 4Middle: A is a schematic diagram of the synthesis of GelMA-DA; DA can be chemically grafted onto the side chains of GelMA in the presence of EDC / NHS, and physically aggregated on the side chains of GelMA through hydrogen bonds and π-π bonds; B is the Fourier transform infrared (FTIR) spectra of GelMA, GD-1 and GD-2. The figure above shows the enlarged image of the characteristic peaks of NH, CN and benzene ring stretching vibration; C is a representative SEM image showing the nanofiber network morphology of GelMA, GD-1 and GD-2 before and after UV cross-linking (5000×, SEM; scale bar: 5μm); D is the diameter of electrospun nanofibers in GelMA, GD-1 and GD-2 before and after UV cross-linking; E is CCK-8 detection showing the proliferation of PDLSCs co-cultured on GelMA, GD-1 and GD-2 on days 1, 3 and 7 (n=3); the results are expressed as mean ± standard deviation, and the data shown in D and E were analyzed by two-way ANOVA, *p<0.05, **p<0.01 and ***p<0.001 indicate statistical differences among the groups.

[0041] Figure 5 Microscopic morphology characterization of 2% DA-modified GelMA fiber networks with ordered orientation (Fiber-A) or random (Fiber-R); Figure 5 Middle: A is a representative SEM image showing the ordered and randomly arranged nanofibers in Fiber-A and Fiber-R (5000×, SEM; scale bar: 5μm), as well as the orientation image of the nanofibers marked by pseudo-color (cyan corresponds to the horizontal direction, red corresponds to the vertical direction), and the yellow arrow indicates the direction of fiber running; B is a representative image of atomic force microscopy (AFM), showing the surface morphology of Fiber-A and Fiber-R, left: fiber network surface morphology; right: three-dimensional visualization of the fiber network morphology.

[0042] Figure 6 The figure is a schematic diagram and cross-sectional morphology of the preparation of the alveolar bone-periodontal ligament dual-phase scaffold based on 3D printing and electrospinning technology of the present invention. Figure 6Middle: A is a biphasic scaffold prepared by 3D printing technology to prepare the bone phase module and the electrospinning technology to construct the fiber phase module, which were then cross-linked by ultraviolet light; B is a representative SEM image showing the natural alveolar bone-periodontal ligament tissue interface. The upper image shows the oriented periodontal ligament ligament, and the lower image is a magnified image showing the periodontal ligament penetrating into the bone tissue (indicated by the white arrow) (upper image: 2500×, SEM; scale bar: 25μm; lower image: 5000×, SEM, scale bar: 10μm); (C) Representative SEM images show the microstructure of the cross-sectional junction of the biphasic scaffold. The magnified image in the lower image shows the oriented nanofibers interwoven throughout the bone phase module (indicated by the white arrow) (top: 10000×, SEM; scale bar: 5μm; bottom: 50000×, SEM, scale bar: 1μm).

[0043] Figure 7 This is a fluorescence image of the in vivo degradation of the biphasic stent. The biphasic stent was labeled with a fluorescent dye and then implanted subcutaneously in the back of a C57 mouse. The changes in fluorescence intensity were observed 4 weeks after surgery. Figure 7 Middle: A is a representative in vivo fluorescence image showing the degradation of the biphasic scaffold at 0, 1, 2, 3 and 4 weeks after subcutaneous implantation; B is a quantitative analysis of the degradation rate of the biphasic scaffold by fluorescence intensity (n=3); the results are expressed as mean ± SD. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0046] In a first aspect, the present invention provides an alveolar bone-periodontal ligament-mimicking biphasic scaffold, the alveolar bone-periodontal ligament-mimicking biphasic scaffold comprising a fiber phase module and a bone phase module constructed on the fiber phase module;

[0047] The fiber phase module is an orderly arranged fiber network scaffold constructed by dopamine-modified gelatin;

[0048] The bone phase module is a gelatin 3D printed scaffold doped with freeze-dried platelet-rich fibrin exudate and nanoclay.

[0049] An embodiment of the present invention provides an alveolar bone-periodontal ligament-imitating biphasic scaffold. The bone phase module of the alveolar bone-periodontal ligament-imitating biphasic scaffold provided by the present invention has the ability to recruit stem cells and promote bone differentiation; the fiber phase module can directionally guide cell arrangement and promote the differentiation of stem cells into periodontal ligament. Each module highly matches the biomechanical characteristics of periodontal soft and hard tissues, and can achieve synchronous repair of periodontal hard and soft tissues, effectively solving the technical problems of the gap between the interface bionics of tissue engineering scaffolds and natural tissues and the poor endogenous regeneration efficiency, and making up for the shortcomings of the prior art.

[0050] In some specific embodiments, the thickness of the fiber phase module is 0.1-0.3 mm, and the thickness of the bone phase module is 4-6 mm.

[0051] In some specific embodiments, the fiber phase module and the bone phase module are compositely connected by ultraviolet cross-linking.

[0052] In a second aspect, based on the same inventive concept, the present invention provides a method for preparing the alveolar bone-periodontal ligament-mimicking biphasic scaffold described in any one of the first aspects, such as Figure 1 As shown, the preparation method comprises the following steps:

[0053] Adding freeze-dried platelet-rich fibrin exudate, nanoclay and gelatin into a first solvent for a first mixing reaction to obtain a 3D printing ink;

[0054] adding dopamine, EDC, NHS and gelatin into a second solvent for a second mixing reaction, and then adding an acetic acid solution for stirring to obtain a dopamine-modified gelatin electrospinning solution;

[0055] The dopamine-modified gelatin electrospinning solution is prepared by an electrospinning method to obtain an ordered fiber network membrane;

[0056] After drying the ordered fiber network membrane, immersing it in a photoinitiator solution, and then performing a first ultraviolet crosslinking to obtain a fiber phase module;

[0057] The 3D printing ink is printed on the fiber phase module through a 3D printing device to construct a bone phase module, and then a second ultraviolet cross-linking is performed to obtain the alveolar bone-periodontal membrane simulated biphasic scaffold.

[0058] The preparation method of the alveolar bone-periodontal ligament imitation biphasic scaffold provided in the embodiment of the present invention is to add freeze-dried platelet-rich fibrin exudate and nanoclay to the gelatin precursor solution for a first mixing reaction, and construct a bone phase module by 3D printing for recruiting stem cells and osteogenic differentiation; dopamine and gelatin are added to an acetic acid solvent for a second mixing reaction to obtain a dopamine-modified gelatin electrospinning liquid, and a fiber phase module composed of an oriented fiber network is obtained by electrospinning technology, which is used to guide the directional arrangement of stem cells and ligament differentiation; cross-linking is induced by ultraviolet light to finally form an alveolar bone-periodontal ligament imitation biphasic scaffold. At the same time, the preparation method is based on the alveolar bone-periodontal ligament imitation biphasic scaffold described in any one of the first aspects, and therefore has at least the beneficial effects of the alveolar bone-periodontal ligament imitation biphasic scaffold described in any one of the first aspects, which will not be repeated here.

[0059] In some specific embodiments, the above preparation method may specifically include the following steps:

[0060] S1. adding freeze-dried platelet-rich fibrin exudate, nanoclay and gelatin to a first solvent for a first mixing reaction, stirring at 900-1200 rpm for 120-150 min at a temperature of 35-40° C. to obtain a 3D printing ink;

[0061] S2. dopamine, EDC (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride), NHS (N-hydroxysuccinimide) and gelatin are added to the second solvent for a second mixing reaction, and stirred at 800-1200 rpm for 6-8 hours at a temperature of 35-40° C.;

[0062] S3. Add acetic acid solution dropwise to the mixed solution obtained in step S2 and stir thoroughly to obtain a dopamine-modified gelatin electrospinning solution;

[0063] S4. The dopamine-modified gelatin electrospinning solution obtained in step S2 is electrospinned to prepare an ordered fiber network;

[0064] S5. The ordered fiber network obtained in step S4 is dried and placed in a crosslinking solution for 6-8h, UV crosslinked for 30-90min, and then washed and dried to obtain a fiber phase module;

[0065] S6. Print the 3D printing ink described in step S1 on the fiber phase module obtained in step S5 through a 3D printing device to construct a bone phase module: then obtain an alveolar bone-periodontal membrane-mimicking biphasic scaffold through UV cross-linking.

[0066] In some specific embodiments, the preparation process of the freeze-dried platelet-rich fibrin exudate in step S1 is: collect 5-10 ml of human upper limb venous blood, centrifuge at 2800-3200 rpm for 10-12 minutes to obtain platelet-rich fibrin, squeeze it with a sterile glass slide to form a film, collect the platelet-rich fibrin exudate and freeze-dry it for 48 hours to obtain freeze-dried platelet-rich fibrin exudate.

[0067] In some specific embodiments, the 3D printing ink in step S1, wherein the mass concentration of the freeze-dried platelet-rich fibrin exudate is 0.1%-1.5%, the nanoclay includes Laponite-XLG, with a mass concentration of 0.5%-3%, and the gelatin includes methacrylamide gelatin (GelMA), the amino substitution degree of the GelMA is 55%-95%, and the mass concentration is 12-22%.

[0068] In some specific embodiments, the dopamine in step S2 includes dopamine hydrochloride with a mass concentration of 1%-3%, EDC and NHS include 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide, and the molar ratio of EDC to NHS is (5-3):1.

[0069] In some specific embodiments, the acetic acid in step S3 includes glacial acetic acid, and the volume content is 27-33 vt%.

[0070] In some specific embodiments, the specific process of step S4 is: by using an oriented receiver drum to collect the oriented electrospinning, the electrospinning process parameters are set to a voltage of 18-25 kV, a distance of 10 to 20 cm between the spinning needle and the receiver, a syringe needle of 18-22 G, an injection speed of 0.3-1.2 ml / h, and an oriented receiver drum speed of 2800-3200 rpm.

[0071] In some specific embodiments, the electrospinning is placed in a drying oven at 35-40° C. for 24-48 hours, and after cutting, it is immersed in an ethanol solution containing a photoinitiator 2959 in a light-proof manner, with a mass concentration of 1-3%. The photoinitiator 2959 includes 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.

[0072] In some specific embodiments, in step S6, the bone phase module is constructed by a 3D printing device, and the diameter of the extruded filament is 0.1-0.4 mm.

[0073] In a third aspect, the present invention provides a use of the alveolar bone-periodontal ligament-mimicking biphasic scaffold described in any one of the first aspect and the second aspect in the preparation of products for treating and repairing soft and hard tissue defects.

[0074] It should be noted that the components and raw materials involved in the alveolar bone-periodontal ligament imitation biphasic scaffold and the preparation method thereof provided in the embodiments of the present invention, unless otherwise specified or specified, can be directly commercially available products or homemade using existing public preparation methods. For example, the raw materials include: GelMA and photoinitiator from Suzhou Yongqinquan Intelligent Equipment Co., Ltd.; nanoclay from BYK Chemical Co., Ltd., and dopamine from Shanghai Aladdin Reagent Co., Ltd.; at the same time, the steps and parameters involved, unless otherwise specified or specified, can be carried out according to the existing processing technology of the alveolar bone-periodontal ligament imitation biphasic scaffold or directly using existing equipment, and the present invention document will not repeat them one by one.

[0075] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0076] Example 1

[0077] This example provides a method for preparing a bone phase module in an alveolar bone-periodontal ligament-mimicking biphasic scaffold without incorporating freeze-dried platelet-rich fibrin exudate (PRFe) based on 3D printing and electrospinning technology, such as Figure 2 As shown, the specific steps include:

[0078] First, GelMA was dissolved in PBS containing a photoinitiator at 37 degrees, and then Laponite powder was added and stirred for 2 hours until fully dissolved to obtain GelMA / Laponite 3D printing ink, in which the mass fraction of GelMA was 15%, the mass fraction of Laponite was 0.5%, 1% and 2% (named GL-0.5, GL-1 and GL-2 respectively, and the GelMA without Laponite was set as the control group, named GelMA), and the mass fraction of photoinitiator 2959 in the PBS solution was 2%. Subsequently, the bone phase module was constructed by a 3D printing device. The working condition parameters of the 3D printing device include: the diameter of the extruded filament is 0.26mm, and the 3D printer parameters are set to: the scaffold size is 10×10×5mm 3 , push-out air pressure 20 bar, needle temperature 25°C, receiving platform temperature 5°C, needle speed 4 mm / s, layer spacing 0.26 mm, and printing filament spacing 1 mm.

[0079] The bone phase module obtained above without incorporation of freeze-dried platelet-rich fibrin exudate (PRFe) was characterized, as shown in FIG. Figure 2 As shown. Figure 2Analysis shows that: Scanning electron microscope images show that the surface of the 3D printed bracket can form a porous structure ( Figure 2 B). Further EDS elemental analysis revealed that Si and Mg elements were evenly distributed on the surface of the bracket, indicating that Laponite was evenly distributed on the 3D printed bracket ( Figure 2 C). Through swelling and degradation experiments, it can be found that as the proportion of Laponite doped increases, the swelling degree of the 3D printed scaffold decreases and the degradation time increases ( Figure 2 D and E). The mechanical properties of the scaffold were tested by uniaxial compression test, and the hardness of the scaffold with different Laponite concentrations was obtained by the first 10% of the stress-strain curve. The results showed that as the proportion of Laponite increased, the mechanical properties of the 3D printed scaffold were enhanced ( Figure 2 F and G).

[0080] Example 2

[0081] Based on the GelMA / Laponite scaffold containing 2% nanoclay obtained in Example 1 above, freeze-dried platelet-rich fibrin exudate (PRFe) was added to prepare a bioactivated GelMA / Laponite scaffold (i.e., the bone phase module in the alveolar bone-periodontal ligament dual-phase scaffold), as shown in FIG. Figure 3 As shown, the preparation method thereof comprises the following steps:

[0082] First, 5 ml of upper limb venous blood was collected from human body and centrifuged at 3000 rpm for 10 min to obtain platelet-rich fibrin. The blood was squeezed with a sterile glass slide to form a membrane. The platelet-rich fibrin exudate was collected and freeze-dried for 48 h to obtain freeze-dried platelet-rich fibrin exudate (PRFe).

[0083] Freeze-dried platelet-rich fibrin exudate (PRFe) was further mixed into the GelMA / Laponite 3D printing ink obtained in Example 1 and stirred for 1 hour to obtain GelMA / Laponite+PRFe 3D printing ink, wherein the mass fraction of freeze-dried platelet-rich fibrin exudate (PRFe) was 1%. Subsequently, a bioactivated GelMA / Laponite scaffold was printed, and the specific printing steps were the same as those described in Example 1.

[0084] The bone phase module obtained above and incorporated with freeze-dried platelet-rich fibrin exudate (PRFe) was characterized, as shown in FIG. Figure 3 As shown. Figure 3 Analysis shows that:

[0085] The bioactivated GelMA / LAP scaffolds can release TGF-1b and BMP-2 continuously for up to 16 days as detected by ELISA. Figure 3C). Then, respectively, through migration ( Figure 3 D and F) and scratch test ( Figure 3 E and D) The results showed that the cell migration rate of the PRFe-loaded group was better. ALP and ARS staining were used to verify its excellent ability to promote osteogenesis ( Figure 3 H and I).

[0086] Example 3

[0087] This example provides an orderly oriented fiber phase module in an alveolar bone-periodontal ligament-mimicking dual-phase scaffold based on 3D printing and electrospinning technology, and the preparation method thereof comprises the following steps:

[0088] Dopamine (DA), EDC (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride), NHS (N-hydroxysuccinimide) and GelMA were added to an acetic acid solution and stirred at 37°C for 6 hours to obtain a dopamine-modified GelMA electrospinning solution, in which the mass fractions of dopamine were 1% and 2% (named GD-1 and GD-2, respectively, and the GelMA without DA modification was set as the control group, named GelMA), the molar ratio of EDC and NHS was 4:1, and the mass fraction of GelMA was 20%. Subsequently, a fiber network was prepared by electrospinning, and the electrospinning process parameters were set as a voltage of 20 kV, a distance of 15 cm from the spinning needle to the receiver, a syringe needle of 18G, a push speed of 1 ml / h, and a rotation speed of 800 rpm for the orientation receiver drum.

[0089] The dopamine-modified GelMA (GelMA-DA) fiber network prepared by the above electrospinning technique was characterized. Figure 4 As shown. Figure 4 Analysis shows that:

[0090] First, the grafting of DA in GelMA-DA was detected by infrared spectroscopy. The results showed that the characteristic peak of the amide group of GelMA (1645 cm -1 and 1537cm -1 NH and CN, respectively), and the characteristic peaks of the benzene ring belonging to dopamine (1018 and 932 cm -1 ), proving that DA-modified GelMA was successfully constructed ( Figure 4 A and B). The DA-modified GelMA fiber network was further constructed by electrospinning technology, and the morphology of the fiber network grafted with different concentrations of dopamine before and after cross-linking was observed by scanning electron microscopy ( Figure 4 C), the changes in fiber diameter before and after fiber network crosslinking show that the dopamine-modified GelMA fiber network showed better structural stability, and the morphology and diameter of GD-2 nanofibers changed the least ( Figure 4 D).

[0091] Example 4

[0092] Based on the 2% DA modified GelMA fiber network obtained in Example 3 above, random (Fiber-R) and ordered oriented (Fiber-A) 2% DA modified GelMA fiber networks were prepared, and the preparation method thereof comprises the following steps:

[0093] Based on the modified GelMA fiber network containing 2% DA obtained in the above Example 3, the rotation speed of the electrospinning receiving drum was adjusted to regulate the orientation of the fiber network. The modified GelMA fiber network containing 2% DA constructed when the rotation speed of the orientation receiver drum was 800 rpm was named Fiber-R, and the modified GelMA fiber network containing 2% DA constructed when the rotation speed of the orientation receiver drum was 3000 rpm was named Fiber-A.

[0094] The microstructure of the ordered (Fiber-A) or random (Fiber-R) 2% DA modified GelMA fiber network was characterized as follows: Figure 5 As shown. Figure 5 The analysis showed that random and oriented dopamine-modified GelMA (GelMA-DA) fiber networks were observed by SEM, and orientation pseudo-colors were assigned (cyan corresponds to horizontal direction, red corresponds to vertical direction; Figure 5 A), the results show that the fibers of the oriented fiber network are mostly in a uniform horizontal direction, indicating that the oriented fiber network was successfully constructed. Atomic force microscopy (AFM) was further used to verify the morphology of random and oriented fiber networks ( Figure 5 B).

[0095] Example 6

[0096] Based on the above-mentioned embodiments 1 to 5, this example provides an alveolar bone-periodontal ligament-like biphasic scaffold based on 3D printing and electrospinning alveolar bone-periodontal ligament-like biphasic scaffold technology, wherein the alveolar bone-periodontal ligament-like biphasic scaffold comprises a fiber phase module and a bone phase module constructed on the fiber phase module; the fiber phase module is an ordered fiber network scaffold constructed of dopamine-modified gelatin; the bone phase module is a gelatin 3D printed scaffold doped with freeze-dried platelet-rich fibrin exudate and nanoclay. Figure 6 As shown, the preparation method specifically comprises the following steps:

[0097] Based on the ordered fiber network scaffold constructed by dopamine-modified gelatin obtained in Example 4, the fiber network was immersed in a photoinitiator solution of ethanol solution containing photoinitiator 2959 for 60 minutes, wherein the mass concentration of photoinitiator 2959 was 2%, and then the ultraviolet cross-linking time was 60 minutes to obtain a fiber phase module. The GelMA / Laponite+PRFe 3D printing ink obtained in Example 2 was printed by a 3D printing device to construct a bone phase module, and the specific printing parameters were the same as those described in Example 1. The ultraviolet cross-linking time was then 30 seconds to obtain a dual-phase scaffold imitating alveolar bone-periodontal membrane.

[0098] The alveolar bone-periodontal ligament-mimicking biphasic scaffold obtained above was subjected to microscopic characterization, such as Figure 6 As shown. Figure 6 Analysis shows that:

[0099] The bone-phase and ligament-phase scaffolds that were screened and optimized step by step were cross-linked by ultraviolet light, and the interwoven structure of the alveolar bone and periodontal ligament of natural periodontal tissue was first observed by scanning electron microscopy ( Figure 6 B), and then observed the interface of the alveolar bone-periodontal ligament dual-phase scaffold, and observed that the nanofibers of the oriented-bone / fiber scaffold were inserted through the bone phase to form an interwoven structure ( Figure 6 C).

[0100] Example 7

[0101] This example also conducted an in vivo degradation experiment on the alveolar bone-periodontal ligament-mimicking biphasic scaffold obtained in Example 6, which specifically included the following process: The in vivo degradation of the biphasic scaffold after implantation into the subcutaneous tissue of the back of C57 mice was analyzed by in vivo imaging. The fluorescent dye (EFL-DYE-R) was loaded into the bone phase module and the fiber phase module and then cross-linked into a fluorescently labeled biphasic scaffold (10 mm long, 10 mm wide, and 3 mm thick). The animal experiment was approved by the Animal Experiment Ethics Committee of the Fourth Military Medical University, and 6 6-8 week old C57 / BL6 mice (purchased from the Animal Experiment Center of the Fourth Military Medical University) were used for this experiment. The surgical steps are as follows: After inducing anesthesia in mice with 2% isoflurane and a small animal anesthesia machine, anesthesia was maintained at a concentration of 1% for the entire operation. A 1 cm full-thickness skin incision was made on the back skin of the mouse, the subcutaneous tissue and muscle were separated, and the fluorescently labeled biphasic scaffold was implanted and tightly sutured. Immediately, 1, 2, 3, and 4 weeks after surgery, the fluorescence intensity in the biphasic scaffolds was detected using a small animal living imager, and the fluorescence intensity was analyzed using LivingImage v4.3.1 software.

[0102] The experimental results are as follows Figure 7 As shown. Figure 7 Analysis shows that: In vivo imaging results show that the fluorescence intensity of the biphasic stent decreases with time. Fluorescence images can still be seen 4 weeks after subcutaneous implantation ( Figure 7 A) to prevent gelatin biomaterials from being absorbed and degraded too quickly in the body. Quantitative results showed that the fluorescence intensity of the biphasic stent continued to decrease 4 weeks after surgery, and the remaining fluorescence intensity was 22.19% of the initial fluorescence intensity. Figure 7 B).

[0103] Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0104] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A dual-phase scaffold imitating alveolar bone and periodontal ligament, characterized in that: The alveolar bone-periodontal ligament-mimicking dual-phase scaffold comprises a fiber phase module and a bone phase module constructed on the fiber phase module; The fiber phase module is an orderly arranged fiber network scaffold constructed by dopamine-modified gelatin; The bone phase module is a gelatin 3D printed scaffold doped with freeze-dried platelet-rich fibrin exudate and nanoclay.

2. The alveolar bone-periodontal ligament-mimicking biphasic scaffold according to claim 1, characterized in that: The thickness of the fiber phase module is 0.1-0.3 mm, and the thickness of the bone phase module is 4-6 mm.

3. The alveolar bone-periodontal ligament-mimicking biphasic scaffold according to claim 1, characterized in that: The fiber phase module and the bone phase module are compositely connected by ultraviolet cross-linking.

4. A method for preparing the alveolar bone-periodontal ligament-mimicking dual-phase scaffold according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: Adding freeze-dried platelet-rich fibrin exudate, nanoclay and gelatin into a first solvent to perform a first physical doping and mixing reaction to obtain a 3D printing ink; adding dopamine, EDC, NHS and gelatin into a second solvent to carry out a second mixed bio-coupling chemical reaction, and then adding an acetic acid solution for stirring to obtain a dopamine-modified gelatin electrospinning solution; The dopamine-modified gelatin electrospinning solution is prepared by an electrospinning method to obtain an ordered fiber network membrane; After drying the ordered fiber network membrane, immersing it in a photoinitiator solution, and then performing a first ultraviolet crosslinking to obtain a fiber phase module; The 3D printing ink is printed on the fiber phase module through a 3D printing device to construct a bone phase module, and then a second ultraviolet cross-linking is performed to obtain the alveolar bone-periodontal membrane simulated biphasic scaffold.

5. The method for preparing the alveolar bone-periodontal ligament-mimicking dual-phase scaffold according to claim 4, characterized in that: The 3D printing ink includes the following components in terms of mass percentage: 0.1%-1.5% of freeze-dried platelet-rich fibrin exudate, 0.5%-3% of nanoclay, 12-22% of gelatin; the remainder is the first solvent; Wherein, the nanoclay includes Laponite-XLG, the gelatin includes methacrylamide gelatin, and the first solvent includes at least one of PBS culture medium, MEM culture medium, PBS solution and MEM solution.

6. The method for preparing the alveolar bone-periodontal ligament-mimicking dual-phase scaffold according to claim 4, characterized in that: The dopamine-modified gelatin electrospinning solution comprises the following components in percentage by mass: Dopamine (1%-3%), EDC / NHS (0.5%; wherein the molar ratio of EDC to NHS is (5-3):1), gelatin 15-25%; the volume concentration of the acetic acid solution is 27-33vt%; the second solvent includes at least one of hexafluoroisopropanol and formic acid; the dopamine includes dopamine hydrochloride.

7. The method for preparing the alveolar bone-periodontal ligament-mimicking dual-phase scaffold according to claim 4, characterized in that: The working condition parameters of the electrospinning method include: collecting the oriented electrospinning by using an oriented receiver roller, the electrospinning process parameters are set to a voltage of 18-25kV, a distance of 10-20cm between the spinning needle and the receiver, a syringe needle of 18-22G, a push injection speed of 0.3-1.2ml / h, and an oriented receiver roller rotation speed of 2800-3200rpm.

8. The method for preparing the alveolar bone-periodontal ligament-mimicking dual-phase scaffold according to claim 4, characterized in that: The working condition parameters of the 3D printing device include: the diameter of the extruded wire is 0.1-0.4mm, and the 3D printer parameters are set to: the bracket size is 10×10×5mm 3 , push-out air pressure 20 bar, needle temperature 25°C, receiving platform temperature 5°C, needle speed 4 mm / s, layer spacing 0.26 mm, and printing filament spacing 1 mm.

9. The method for preparing the alveolar bone-periodontal ligament-mimicking dual-phase scaffold according to claim 4, characterized in that: The photoinitiator solution is an ethanol solution containing photoinitiator 2959, and the mass concentration of the photoinitiator 2959 is 1-3%; The working condition parameters of the first ultraviolet cross-linking include: the ultraviolet cross-linking time is 50 to 70 minutes; the working condition parameters of the second ultraviolet cross-linking include: the ultraviolet cross-linking time is 20 to 40 seconds.

10. Use of the alveolar bone-periodontal ligament-mimicking biphasic scaffold according to any one of claims 1 to 9 in preparing products for treating and repairing soft and hard tissue defects.